PENGARUH KOMPOSISI SUBSTRAT CAMPURAN KOTORAN SAPI DAN JERAMI PADI TERHADAP PRODUKTIVITAS BIOGAS PADA DIGESTER SEMI KONTINYU - Agus Haryanto; Oktafri Oktafri; Sugeng Triyono; Muhammad Rizki Zulyantoro (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
This study aims to determine the effect of substrate composition on biogas productivity from a mixture of cow dung and rice straw on semi-continuous digester. Rice straw used taken from Way Galih Village, South Lampung, and fresh cow dung was obtained from Laboratory in Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. Biogas starter is filled with 26 liters of cow dung and water in 1: 1 ratio comparison based on weight. Then its being left for 4 day for stabilization. If the biogas production is stable, then substrate will be added with loading rate 0.5 liters / day, with 6 compositions of different cow dung and rice straw from the ratio of cow dung and elephant grass based on the following TS: P1 (75% : 25%), P2 (70% : 30%), P3 (65% : 35%), P4 (60% : 40%), P5 (55% :45%) dan P6 (50% : 50%). Parameters which observed in this study include daily temperature, pH, TS and VS substain, daily biogas volume, biogas productivity, and biogas quality. The results showed that in 6 treatments had the same average pH of 6,8. The average temperatures on the morning were 26,37 °C, 26,29 °C, 26,24 °C, 26,22 °C, 26,28°C, and 26,26 oC while in the afternoon respectively 29,58 °C, 29,47 °C, 29,48 °C, 29,49 °C,2 9,57 °C, and 29,61 oC. The total biogas production is 185,5 liter, 284,25 liter, 186,85 liter, 448,15 liter, and 108,55 liter, respectively for P1, P2, P3, P4, P5 and P6 with biogas productivity sequentially is 378,66 l/kg VSr, 684,87 l/kg VSr, 378,76 l/kg VSr, 1498,02 l/kg VSr, 587,21 l/kg VSr and 395,95 l/kg VSr. The quality of biogas through the flame test produces a bright blue flame color.